Campylobacteriosis – the epidemiological situation in Poland and other European countries - Nowicka, Sylwia; Ździebło , Magdalena; Skrzypek , Kinga; Kosikowska, Urszula; Malm, Anna (Polish Journal of Public Health, 2013)
Food poisoning and infections are the most common dis-orders that now occur all over the world. One of the human epidemiologic factors of gastrointestinal tract disorders and diseases are Campylobacter spp. rods, among which Campylobacter coli and C. jejuni are the most significant. These bacteria are able to cause a contagious disease called the campylobacteriosis. Consumption, especially of poultry meat without an adequate heat treatment, became the grea- test cause of an illness, and that was the reason why Campylobacter spp. were classified as a food-borne zoonotic pathogens. Nowadays, Campylobacter spp. and many other bacteria prove to be more and more resistant to antibiotics and chemotherapeutics. Drug resistance in this group of micro- organisms begins to emerge globally and due to this fact, the WHO described it as a serious problem. Most of the Campylobacter spp. strains are resistant to cephalothin and fluoroquinolones, but are sensitive to a nalidixic acid. Macrolides and tetracyclines are usually used with more complicated infection cases. However, the increasing C. coli and C. jejuni resistance to quinolones, tetracyclines and erythromycin, influences the effectiveness of antibiotic therapy. Disturbing is the fact that in the European Union over 10,000 cases of campylobacteriosis are reported – about 6 infections per 100,000 population, often with fatal end (in the period of 2006-2011, 266 people died). Because of signs of Campylobacter spp. infection, 1027 people in Poland were hospitalized between 2004-2011, and on the 15th December 2012 the campylobacteriosis incidence rate exceeded the threshold of 1.00 per 100,000 population.Epidemiologic data clearly indicate the significance of campylobacteriosis problem in Poland. The disease occupies higher and higher places in general classification of infectious diseases appearing in our country